The diverse oncogenic and tumour suppressor roles of p63 and p73 in cancer: a review by cancer site - Orzol, Paulina; Holcakova, Jitka; Nekulova, Marta; Nenutil, Rudolf; Vojtesek, Borivoj; Coates, Philip J (Histology and histopathology, 2015)
p63 and p73, the two other members of the p53 family, were identified almost 15 years ago. Here, we review their potential use for diagnosis, prognosis and prediction of response to therapy in various cancers. The two genes show distinct expression patterns in both normal and cancer tissues and each gene gives rise to multiple protein isoforms with different activities, including those with tumour-suppressor or oncogenic effects. Despite such complexity, some common themes emerge; p63 is commonly overexpressed as the ΔNp63 isoform and sometimes associated with TP63 amplification, whereas p73 is often reduced (by methylation or gene loss), or there is an increase in the ratio of ΔNp73 to TAp73. These generalisations do not apply universally; TAp63 is overexpressed in haematological malignancies, TP63 mis-sense mutations have been reported in squamous cancers and TP63 translocations occur in lymphomas and some lung adenocarcinomas. There are associations with disease prognosis and response to specific therapies in individual cancer types for both p63 and p73, making their analysis of clinical relevance. We also discuss their utility for aiding in differential diagnosis, which has been demonstrated for p63, but not yet for p73. Throughout, we highlight the discrepant nature of many studies due to the variable methodologies employed, the lack of systematic evaluation of isoforms and the problems of poor antibody characterization and cross-reactions within the p63/p73 family. Finally, we emphasize the value of recently developed isoform-specific reagents that have clear advantages for the study of p63 and p73 experimentally and clinically.
Keywords: tumor supresorové geny; DNA-Binding Proteins; regulace genové exprese u nádorů; Humans; DNA vazebné proteiny; Transcription Factors; Biomarkers, Tumor; nádorové supresorové proteiny; Genes, Tumor Suppressor; Carcinogenesis; Female; mutace; onkogeny; Tumor Protein p73; jaderné proteiny; lidé; Oncogenes; proliferace buněk; Tumor Suppressor Proteins; nádorové biomarkery; ženské pohlaví; bodová mutace; Male; karcinogeneze; modely genetické; Cell Proliferation; Nuclear Proteins; Neoplasms; Point Mutation; nádory; Models, Genetic; transkripční faktory; protein p73; Mutation; mužské pohlaví; Gene Expression Regulation, Neoplastic